(3GdHgLI GdeQVjI aj TQM GdCdajIs - (3GdbQTj GdgGTej, HgGA GdOjf, GHf Ybjd, GHf Ybjd, YHO Gddg Hf YHO GdQMef Hf YHO Gddg GdbQTj GdgGTej, J (B769(3g` (B1367(3es
(3ChdgG (B:s
(3ChdgG(B: (3CMeOc Gddge Ydi fYeGFc (B... (3gPG TQM dWja eRLJg HCdajI GHf eGdc egPH GdebGUO hGVM GdeSGdc jHjf eQGOfGs
(3BNQgG (B:s
(3BNQgG(B: (3habO CJi YUQ aj CYUQ aOhfc eDdaG cCfg SHjcI YSLO Ch (B.. (3efVO HQR aj EHGf GdeTGQ hJejR YfOg (B.. (3Chdj GdCdHGH hbO bGd GHf YHGS eG ChJj YGde YdeG EdG hgh TGH(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B4: 96s
(3cTa GdXfhf, L (B1: 152s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs